2001
DOI: 10.5935/0305-7518.20010027
|View full text |Cite
|
Sign up to set email alerts
|

Should nutritional status evaluation be included in the initial needs assessment of leprosy patients with disability prior to socio-economic

Abstract: Because of the large numbers of leprosy patients with disability and the lirnited resources available, it is important that socio-econornic rehabilitation (SER) is targeted towards those who are most in need. Towards this purpose, current assess ments of leprosy patients prior to initiating SER inc1ude the evaluation of income, assets and household possessions. Conspicuously absent is the nutritional assessment of the patient. In the absence of weight loss associated with illness, population studies indicate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…Similar results have been reported in other studies [16, 29]. In contrast, a high degree of malnutrition has been observed in studies conducted in India (BMI < 17 kg/m 2 ) [30, 31]. These discordant data occurred due to the different populations studied and the different feeding patterns of each of these populations.…”
Section: Discussionsupporting
confidence: 87%
“…Similar results have been reported in other studies [16, 29]. In contrast, a high degree of malnutrition has been observed in studies conducted in India (BMI < 17 kg/m 2 ) [30, 31]. These discordant data occurred due to the different populations studied and the different feeding patterns of each of these populations.…”
Section: Discussionsupporting
confidence: 87%
“…Similar results were reported by Chaptini and Marsham [ 23 ], Moura et al [ 34 ], and Canicoba et al [ 35 ]. However, Vaz et al [ 36 ] and Khandapani and Mishra [ 37 ] reported a malnutrition rate of 57% among Indian patients with leprosy. This difference may be explained by the lower poverty rate in Latin America compared with India, where the frequency of malnutrition is higher.…”
Section: Discussionmentioning
confidence: 99%